First report of Aelurostrongylus abstrusus in domestic land snail Rumina decollata, in the Autonomous city of Buenos Aires - Cardillo, Natalia Marina (2014)
Aelurostrongylus abstrusus (Railliet, 1898) is a worldwide distributed lungworm that affects wild and domestic cats, causing bronchopneumonia of varying intensity. Cats became infected by eating slugs and snails with third infective stage larvae (L3). The aim of the study was to describe the presence of A. abstrusus in R. decollate snails. R. decollata specimens and samples of cats’ faeces were collected from the open spaces of a public institution of Buenos Aires city, inhabited by a stray cat population. Cats’ faeces were processed by Baermman´s technique and snails were digested in pool, by artificial digestion method. First stage larvae of A. abstrusus were recovered from 35.30 % (6/17) of the sampled faeces. An 80 % (20/25) snails pools were positive for the second and third larval stages. Mean value of total larvae recovered per pool was 150.64 and mean value of L3/pool was 93.89. This is the first report of the development of A. abstrusus infective larvae in R. decollate snail as intermediate host, since the relationship between high levels of infection in snails and in cats’ faeces could be demonstrated in cats’ habitat.